Aeroponic systems: A unique tool for estimating plant water relations and NO3 uptake in response to salinity stress. (29th March 2021) - Tafesse, Endale Geta; Aidoo, Moses Kwame; Lazarovitch, Naftali; Rachmilevitch, Shimon
Abstract: The study of transpiration, water, and nutrient uptake during abiotic stress in the root zone is hindered because of the hidden nature of the root zone. In this study, a modified aeroponic system was used to evaluate whole plant transpiration, nitrate and water uptake in the growth and development of tomato plants in response to salinity. Tomato seedlings were exposed to three levels of salinity (1.5, 4.5, and 9 dSm −1 ) and three levels of nitrate (1, 4, and 8 mM NO3 ) in a separate experiments conducted concurrently. Whole plant transpiration, water and nitrate uptake were estimated. Our study revealed that ~30 to 35 days after treatment (DAT), water uptake rate per plant increased from a common initial rate of about 0.05 to 1.1, 0.6, and 0.4 kg/day at 1.5, 4.5, and 9 dSm −1 respectively. The NO3 uptake rates in tomatoes grown in 1 and 4 mM NO3 were 5.5 and 22% respectively, of the uptake of tomatoes grown in 8 mM NO3 . The estimation of nitrate uptake and lower sensitivity to salinity stress in the aeroponic showed the effectiveness and cost efficiency of the system in the cultivation of vegetables during abiotic stresses. The novelty of the system described is the continuous estimation of root and nutrient uptake by the whole plant at any given time.